Country Neighbors - Brown, Alice (Saga Egmont, 2022)
These sixteen short stories are packed full with charming characters and vibrant prose. Each of the tales are based in New England and primarily centered on strong female protagonists who face various hurdles in their relationships. Alice Brown is an American novelist and short-story writer. She is best known for her tales about New England and as a writer of local colour stories. Born in New Hampshire in 1857, Brown\'s stories often portray a female protagonist in a domestic setting. Her first novel, \'Stratford-by-the-Sea\', was published in 1884. It cemented Brown as part of the Boston literary scene, but by the time she died in 1948 (aged 91), many of her stories had been forgotten about and were no longer being published.